Memperkuat Sinergi Antara Program Studi Dengan Lembaga Sertifikasi Dalam Meningkatkan Kualitas Lulusan - Khairil, Khairil; Ramadani, Tri; Fatimah, Dimas Mekar Ayu; Handayani, Setiaji Ayu; Ningrum, Endah Puspa (Jurnal Dehasen Mengabdi, 2024)
Dehasen University and the Multimatics Certification Institute need to provide a curriculum that is relevant to the needs of the job market.Through partnerships with certification institutions that are recognized nationally or internationally, apart from that, certification institutions must also ensure that universities provide access for students to obtain professional certification that is widely recognized. However, to achieve all of this, study programs and certification institutions need strong cooperation, and Studies must also monitor developments in their industry so that they can adjust their learning strategies. Universities and certification institutions must ensure that their graduates are ready to be deployed in the world of work, and that they prepare future generations.